The Essence of Islamic Education: The Paradigm of Knowledge, Faith, and Action - Sunardi, Sunardi; Solechan, Solechan; Ubaidillah, Ubaidillah; Waenasae, Rusdee; Kamali, Ahmad Nur (Perkumpulan Dosen Tarbiyah Islam Indonesia, 2025)
This research aims to review the nature of Islamic education by emphasising the integration of three fundamental aspects, namely science, faith, and charity. The focus of the research is directed at efforts to formulate a more holistic paradigm of Islamic education to be able to answer the challenges of moral degradation, spiritual crisis, and fragmentation of educational orientation, which often only focus on cognitive aspects. The method used is qualitative research with a library research approach. Data were obtained through a review of classical and contemporary literature, including the works of Al-Ghazali, Syed Muhammad Naquib al-Attas, and some modern thinkers, then analysed using content analysis techniques to find patterns, meanings, and conceptual synthesis. The results show that true Islamic education must combine science as a means of knowing God, faith as a spiritual and moral foundation, and charity as a real actualisation of both. Knowledge without faith has the potential to give birth to arrogance, while faith without charity makes no real contribution. The contribution of this research lies in the affirmation of an integrative Islamic education paradigm, which places humans as spiritual, intellectual and social beings at once. The findings can serve as a conceptual basis for the development of a value- and character-based Islamic education curriculum, as well as enriching the academic discourse on holistic education in an Islamic perspective.